2023
DOI: 10.1155/2023/4851416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Incorporation of Virgin Coconut Oil Byproduct in the Optimization Process of a Baked Snack

Abstract: Snack consumption contributes to the prevalence of noncommunicable diseases because snacks contain high quantities of fat, sodium, and sugar. It is possible to reformulate these foods to improve their nutritional composition by incorporating coconut byproducts. This study aims to improve the nutritional profile of a snack by adding coconut flour to it. A Box–Behnken design was used to study the effects of coconut flour (40-60%), baking time (15-20 min), and temperature (140-160°C) on the physicochemical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Several other applications of SCF in food products like crispy waffles, pasta, biscuits, muffins, and cookies have been reported in the past three years as reported in Table 1. 69–74 Nowadays, the application of nanotechnology in food processing holds tremendous potential. 75 The author reported that during frozen storage of yogurt, the total bacterial count and the viability of Bifidobacterium bifidum , Bifidobacterium breve , Streptococci and Lactobacilli were enhanced by the addition of SCF nanoparticles with sizes ranging from 81.96 nm to 83.53 nm.…”
Section: Application Of Scm and Scf In Food Formulationmentioning
confidence: 99%
“…Several other applications of SCF in food products like crispy waffles, pasta, biscuits, muffins, and cookies have been reported in the past three years as reported in Table 1. 69–74 Nowadays, the application of nanotechnology in food processing holds tremendous potential. 75 The author reported that during frozen storage of yogurt, the total bacterial count and the viability of Bifidobacterium bifidum , Bifidobacterium breve , Streptococci and Lactobacilli were enhanced by the addition of SCF nanoparticles with sizes ranging from 81.96 nm to 83.53 nm.…”
Section: Application Of Scm and Scf In Food Formulationmentioning
confidence: 99%
“…The incorporation of byproducts of the food industry into the development of new food products is a good strategy to enhance the nutritional quality and possible health benefits to the consumer. Coconut flour, a byproduct of the coconut oil industry, has been used to successfully replace (at a 20% level) wheat flour in the preparation of a wheat flourbased tortilla with higher nutritional quality and fiber content [14], and for the production of a baked snack [15]. Another byproduct, rich in insoluble fiber and bioactive compounds, is brewers' spent grain (BSG), already used to create ingredients for different food matrices.…”
Section: Introductionmentioning
confidence: 99%